2017
DOI: 10.1038/srep45479
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and proteomic studies reveal acaricidal mechanism of octadecanoic acid-3, 4 - tetrahydrofuran diester against Sarcoptes scabiei var. cuniculi

Abstract: In our previous study, a new compound, octadecanoic acid-3, 4-tetrahydrofuran diester, possessing potent acaricidal activity was obtained from neem oil. This study performed RNA-seq transcriptomics and iTRAQ proteomics to uncover the acaricidal mechanism of the compound against Sarcoptes scabiei var. cuniculi. The results of transcriptomics indicated that after treatment with octadecanoic acid-3, 4-tetrahydrofuran diester, genes related to “Energy metabolism” were significantly up-/down-regulated, including ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Previously, [44] also investigated that the crude extract of Thalictrum javanicum and their chief derivatives oleic acid showed strong mosquitocidal activity against the dengue filarial vector. Similarly, octadecanoic acid-3, 4-tetrahydrofuran diester displayed significant alteration in the oxidative phosphorylation pathway in the Itch mite Sarcoptesscabiei [45,46]. In support of the above findings, all these compounds might play a major role in delivering larvicidal, enzyme inhibition, and antibacterial activity against the mosquito vectors and microbes.…”
Section: Discussionsupporting
confidence: 63%
“…Previously, [44] also investigated that the crude extract of Thalictrum javanicum and their chief derivatives oleic acid showed strong mosquitocidal activity against the dengue filarial vector. Similarly, octadecanoic acid-3, 4-tetrahydrofuran diester displayed significant alteration in the oxidative phosphorylation pathway in the Itch mite Sarcoptesscabiei [45,46]. In support of the above findings, all these compounds might play a major role in delivering larvicidal, enzyme inhibition, and antibacterial activity against the mosquito vectors and microbes.…”
Section: Discussionsupporting
confidence: 63%
“…The assessment of the acaricidal activity of specific compounds against mites is usually performed in vitro . Filter paper (mites were placed on the filter paper, and the tested solutions were sprayed to mites) (Nong et al, 2012 ; Seddiek et al, 2013 ; Gu et al, 2014 ) and liquid paraffin (mites were placed into the solution diluted in liquid paraffin) (Deng et al, 2012 ; Hu et al, 2015 ; Song et al, 2017 ) are the two most frequently used methods. For the filter paper method, it is hard to identify and calculate the mortality under the microscope because mites move very quickly and are scattered around if the acaricidal activity of specific compounds is not very strong and mites cannot be killed quickly; additionally, the poor optical transparency of filter paper also increases the difficulty of observation.…”
Section: Discussionmentioning
confidence: 99%
“…canis homogenate supernatant, with relative high expression (Morgan et al, 2016 ), and was identified as an antigenic protein (Morgan et al, 2017 ). Recent evidence confirmed that enolase was the target protein of an acaricide named octadecanoic acid-3, 4-tetrahydrofuran diester and that this compound interferes with the energy metabolism of S. scabiei (Song et al, 2017 ). But beyond that, no research has been conducted on S. scabiei enolase, despite its potential importance in S. scabiei .…”
Section: Introductionmentioning
confidence: 98%
“…Pesticides have several insecticidal mechanisms but primarily kill by interfering with enzyme activity related to insect metabolism 19 , 25 . AChE, related to the vital movements of insects, plays an important role in insect neural conduction 40 , and the inhibition of AChE is one of the modes of action of many insecticides, such as organophosphates and carbamates.…”
Section: Discussionmentioning
confidence: 99%